A clinical view on the development of technology‐based tools in managing Parkinson's disease. Issue 9 (7th June 2016) - Maetzler, Walter; Klucken, Jochen; Horne, Malcolm
ABSTRACT: Recently, quantitative, objective, and easy‐to‐use technology‐based tools that can assess PD features over long time periods have been developed and generate clinically relevant and comparable patient information. Herein, we present a clinician's view on technological developments that have the potential to revolutionize clinical management concepts in PD. According to prominent examples in clinical medicine (e.g., blood glycosylated hemoglobin and blood pressure), we argue that the consideration of technology‐based assessment in the clinical management of PD must be based on specific assumptions: (1) It provides a valid and accurate parameter of a clinically relevant feature of the disease; (2) there is confirmed evidence that the parameter has an ecologically relevant effect on the specific clinical application; (3) a target range can be defined wherein the parameter reflects the adequate treatment response; and (4) implementation is simple to allow repetitive use. Currently, there are no technology‐based tools available that fulfil all these assumptions; however, assessments of akinesia, dyskinesia, motor fluctuations, physical inactivity, gait impairment, and postural instability seem relatively close to the specifications described. An iterative process of integration is recommended to bring technology‐based tools into clinical practice. © 2016 International Parkinson and Movement Disorder Society